TRANSFORMASI KERJA HYBRID DAN INOVASI MANAJEMEN: STRATEGI BARU UMKM LAMPUNG DI ERA DIGITAL - Rinaldi Bursan (Yayasan Nusantara Hasana Berdikari, 2025)
This study aims to analyze the influence of hybrid work, digital readiness, and business leadership on management innovation among MSMEs in Lampung Province. The background of this study is based on changes in post-pandemic work patterns that require MSMEs to transform structurally and managerially to remain competitive. The study used a mixed methods approach, with quantitative data obtained from 150 MSME respondents through questionnaires and qualitative data through in-depth interviews. Analysis was conducted using multiple linear regression and data triangulation. The results show that all three independent variables (hybrid work, digital readiness, and business leadership) have a positive and significant effect on management innovation, with hybrid work being the most dominant variable. Furthermore, work efficiency emerged as an important mediating pathway in the relationship between hybrid work and management innovation. The qualitative findings reinforce that successful innovation depends on work system flexibility, technological readiness, and a participatory leadership style. This study recommends increasing digital capacity and adaptive leadership as policy strategies for MSME development based on management transformation.